Parental Self-Awareness Management Towards Children with Gadget Addiction - Leni Rozani; Ferasinta Ferasinta (Health and Technology Journal (HTechJ), 2025)
Prolonged gadget exposure significantly impairs children’s emotional regulation and social adaptability. Such challenges underscore the critical role of early intervention in realigning developmental trajectories and equipping children with adaptive skills for managing frustration and interpersonal engagement. Effective parental self-awareness management entails deliberate strategies to regulate screen time while enriching children’s environments with non-digital stimuli. The research aims to determine the management of parental self-awareness towards children who are addicted to gadgets. The research design is qualitative with a phenomenological method. Collecting data by interviews and observations. Based on the results of interviews with informants, four themes were obtained that explained the research problem. The themes obtained are based on parents' experiences managing self-awareness in children addicted to gadgets. The themes obtained are (1) the use of gadgets in everyday life, (2) characteristics of gadget dependence, (3) strategies to optimize gadget use, and (4) strategies to reduce gadget dependence. Management of parental self-awareness towards children addicted to gadgets, namely by supervising children when playing with gadgets, giving children time limits so they do not overdo it, and directing them to educational websites that children can use. For busy working parents, it is recommended that they still be able to control the intensity (duration and frequency) of gadget use by only giving them gadgets when parents are at home and controlling the activities (playing games or accessing the internet) children do with gadgets.